Understanding and improving the language of business: How accounting and corporate reporting research can better serve business and society - Rolf Uwe Fülbier; Thorsten Sellhorn (Journal of Business Economics, 2023)
Financial accounting, the core of corporate reporting, is often characterized as the 'language of business'. Over the last roughly 100~years, and using an evolving set of theories, methods, and data, scholarly work in this area has been contributing to our understanding of this language and how to improve it. This paper seeks, first, to characterize the field with a focus on its evolution in the German-speaking area, where, like elsewhere, normative research traditions interested in improving practice have been making way for positivist approaches that seek a detached understanding of 'what is.' Second, we discuss the changing users and institutional parameters that are reshaping corporate reporting, followed by our personal view of 'wicked' societal problems and challenges that corporate reporting might be able to help alleviate. Finally, we discuss directions in which research might evolve in order to address these issues, in order to make corporate reporting more useful for serving not only economic actors, but also society and the environment more broadly.
Keywords: 650; Accounting research; Digital transformation; Research assessment; Sustainability reporting; Societal relevance; Transparency